The associations between resilience and socio-demographic factors in parents who care for their children with congenital heart disease - Amy E. Delaney; Mei Rosemary Fu; Melissa L. McTernan; Audrey C. Marshall; Jessica Lindberg; Ravi R. Thiagarajan; Zhuzhu Zhou; Jeibei Luo; Sharon Glazer (Elsevier, 2022)
Objective: To examine the resilience of parents of children with congenital heart disease and to investigate socio-demographic factors that may influence parents' resilience. Methods: This is a web-based survey study using a cross-sectional design. A purposive sampling method was utilized to recruit 515 parents who care for children with congenital heart disease. Resilience was assessed using the Dispositional Resilience Scale-Ⅱ. Based on expert-interviews, a questionnaire was designed to collect socio-demographic data. Descriptive statistics, factor analysis, and linear regressions were used to analyze data. Results: A total of 413 parents completed the survey study. The mean resilience score was 3.75 (SD = 0.61; range = 1.89-4.89) with higher scores indicating higher resilience. The linear regression models demonstrated that parents who had lower education levels and lower gross household income had lower resilience (P < 0.05). Conclusions: Parents reported resilience that reflected their ability to cope with stressful events and mitigate stressors associated with having and caring for children with congenital heart disease. Lower education levels and lower gross household income are associated with lower resilience. To increase parents' resilience, nursing practice and nurse-led interventions should target screening and providing support for parents at-risk for lower resilience. As lower education level and financial hardship are factors that are difficult to modify through personal efforts, charitable foundations, federal and state governments should consider programs that would provide financial and health literacy support for parents at-risk for lower resilience.